The sermon and the African American literary imagination - Hubbard, Dolan, 1949- (University of Missouri Press, 1994)
Characterized by oral expression and ritual performance, the black church has been a dynamic force in African American culture. In The Sermon and the African American Literary Imagination, Dolan Hubbard explores the profound influence of the sermon upon both the themes and the styles of African American literature. Beginning with an exploration of the historic role of the preacher in African American culture and fiction, Hubbard examines the church as a forum for organizing black social reality. Like political speeches, jazz, and blues, the sermon is an aesthetic construct, interrelated with other aspects of African American cultural expression. Arguing that the African American sermonic tradition is grounded in a self-consciously collective vision, Hubbard applies this vision to the themes and patterns of black American literature. With nuanced readings of the work of Frederick Douglass, Frances Ellen Watkins Harper, James Weldon Johnson, Zora Neale Hurston, Ralph Ellison, James Baldwin, and Toni Morrison, Hubbard reveals how the African American sermonic tradition has influenced black American prose fiction. He shows how African American writers have employed the forms of the black preaching style, with all their expressive power, and he explores such recurring themes as the quest for freedom and literacy, the search for identity and community, the lure of upward mobility, the fictionalizing of history, and the use of romance to transform an oppressive history into a vision of mythic transcendence. The Sermon and the African American Literary Imagination is a major addition to the fields of African American literary and religious studies.
Keywords: American literature -- African American authors -- History and criticism.; Sermons, American -- African American authors -- History and criticism.; Fiction -- Religious aspects -- Christianity.; African Americans in literature.; Christianity and literature.; African Americans -- Religion.; Science fiction -- Religious aspects -- Christianity.; Littérature américaine -- Auteurs noirs américains -- Histoire et critique.; Sermons américains -- Auteurs noirs américains -- Histoire et critique.; Science-fiction -- Aspect religieux -- Christianisme.; Noirs américains dans la littérature.; Christianisme et littérature.; Noirs américains -- Religion.; LITERARY CRITICISM -- American -- General.; Science fiction -- Religious aspects -- Christianity; African Americans in literature; African Americans -- Religion; American literature -- African American authors; Christianity and literature; Fiction -- Religious aspects -- Christianity; Sermons, American -- African American authors; Rezeption; Literatur; Predigt; Schwärze; USA; Amerikaans.; Preken.; Letterkunde.; Noirs américains -- Dans la littérature.; Roman -- Aspect religieux.; English literature -- By -- Black persons; United States; Fictional Work; Fiction; Criticism, interpretation, etc.; Fiction.; Romans.